MushkilÄt al-á¹¬alabah fÄ« QirÄâ€™at al-Nuá¹£Å«á¹£ al-Ê¿ArabÄ«yah Ê¿alÃ¡ AsÄs Naáº“arÄ«yat Muá¸¥ammad Ê¿AlÄ« al-KhÅ«lÄ« - Restu Budiansyah Rizki (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
This study aims to describe the problems that students face when reading Arabic texts based on Muhammad Ali Al Khuli's theories. The qualitative descriptive field method was used in this study. Data collection methods included: (1) observation, (2) questionnaire, and (3) interview methods. Data analysis methods in this study were based on Miles and Huberman's methods, which involve 4 steps: (1) data collection, (2) data reduction, (3) data presentation, and (4) data conclusion. Meanwhile, data validity testing in this study used triangulation methods from both data sources and data collection. The results of this study showed that the problems faced by students in reading Arabic texts include moving backward, emplacement, focusing, confusion, preparation, boredom, remembering, taking notice, attention, and repetition problems.